Revision of Semiodera Chamberlin, 1919 (Polychaeta: Flabelligeridae) - Salazar-Vallejo, Sergio I. (Zootaxa, 2012)
Some flabelligerid bodies are modified into a thick thorax and a long, thinner abdomen, or cauda; the thorax usually hassome sediment particles cemented forming a dorsal shield, and these flabelligerids have been found boring into consoli-dated sediments or calcareous substrates. Two species, Pherusa inflata (Treadwell, 1914) and P. parmata (Grube, 1877),are frequently recorded from many different environmental conditions and localities. The study of all type or non-typematerials of similar flabelligerids had several results: 1) The species with bodies modified into thorax and cauda, usuallycarrying a dorsal shield, are removed from Pherusa Oken, 1807; 2) Two body patterns are recognized on the basis of thetype of neurochaetae in transitional chaetigers (3–5), and on the development of the caudae; 3) Semiodera Chamberlin,1919 is redefined to include species with a dorsal shield variously developed, pseudocompound transitional chaetae, andcaudae usually cylindrical with few neurohooks; 4) Daylithos n. gen., includes species with well-developed dorsal shield,multiarticulate or aristate transitional neurochaetae, and caudae usually depressed with few to many neurohooks; 5) Semi-odera includes Semiodera caribea (Grube & Ørsted in Grube, 1859) new spelling, n. comb. (type species), S. blakei n.sp., S. curviseta (Caullery, 1944) n. comb., S. dubia (Treadwell, 1929) n. comb., S. glynni n. sp., S. inflata (Treadwell,1914) n. comb., S. laevis (Stimpson, 1856) n. comb., S. mezianei n. sp., S. nishii n. sp., S. salazarae n. sp., S. tenera(Grube, 1868) n. comb., S. tovarae n. sp., S. treadwelli n. sp. and S. villalobosi n. sp.; 6), Daylithos n. gen. includes Day-lithos parmatus Grube, 1878 n. comb. (type species), D. amorae n. sp., D. cinctus (Haswell, 1892) n. comb., D. dieteri n. sp., D. iris (Michaelsen, 1892) n. comb., and D. nudus (Caullery, 1944) n. comb.